Long noncoding RNA LINC00460 promotes carcinogenesis via sponging miR‐613 in papillary thyroid carcinoma - Feng, Li; Yang, Bin; Tang, Xiao‐Di (Journal of cellular physiology, 2019)
Long intergenic noncoding RNA 460 (LINC00460) has been identified as a critical regulator for multiple types of cancers. However, the biological role and underlying mechanism in human papillary thyroid carcinoma (PTC) still remain unclear and need to be uncovered. This study was aimed to ascertain the biological role and molecular mechanism of LINC00460 in PTC progression. Our findings revealed that the level of LINC00460 was significantly upregulated in PTC tissues and cell lines, which was positively correlated with advanced tumor–node–metastasis (TNM) stage and lymph node metastasis. Cellular experiments exhibited that knockdown of LINC00460 decreased proliferative, migratory, and invasive abilities of PTC cells. Mechanism assays noted that knockdown of LINC00460 suppressed cell proliferation, migration, and invasion, and inhibited expression of sphingosine kinase 2 (SphK2, a target of miR‐613) in PTC cells, at least in part, by regulating miR‐613. These findings suggested that LINC00460 could function as a competing endogenous RNA to regulate SphK2 expression by sponging miR‐613 in PTC. Targeting LINC00460 could be a promising therapeutic strategy for patients with PTC. The present study first demonstrated that the expression of long intergenic noncoding RNA 460 (LINC00460) was upregulated in papillary thyroid carcinoma (PTC) tissues and cell lines. And the elevation of LINC00460 was correlated with advanced tumor–node–metastasis (TNM) stage and lymph node metastasis. Our results also revealed that the oncogene LINC00460 promoted PTC progression via partly regulating miR‐613/sphingosine kinase 2 (SphK2) axis. These findings suggested that the LINC00460/miR‐613/SphK2 might act as a novel therapeutic target for the treatment of PTC.